Genealogi Kemenangan Partai Nasional Indonesia Dalam Pemilu 1955 di Bali - Estepan br. Peranginangin, Fernanda; ., Sulandjari (Humanis; Vol 21 No 1 (2017), 2017)
The Indonesian National Party (PNI) emerged as the winner of the first Indonesian elections in 1955. Amidst the conditions of the largely illiterate and politically blind people the PNI triumphal process became an interesting thing to reveal. Through the use of Genealogy Foucault this study reveals the hidden power-knowledge relation within the public discourse, which was captured by the political community and the PNI-backed society in the PNI triumphal process in the 1955 Election in Bali. There are three research questions posed in this study, whose answers are sought using the help of Kuntowidjoyo's historical political and intellectual methodology. It is also used to assist the critical social science theory of poststructuralism, especially Foucault's theory of truth-power-discourse relation. The theory is used as the basis for thinking in digging and reconstructing the data and placed also in the framework of the approach of post-refluxism history of Foucault. In this way, the study was able to produce three conclusions from each research question, which was then raised to a conclusion essence, that the PNI was essentially selective about the discourse that would be chosen to be the power that would allow the PNI to emerge as the winner in Election 1955. Any discourse considered to be political advantage, captured the hidden knowledge relations in it, then on that basis creates a new discourse which is considered a truth. Their selectivity in choosing the discourse, ultimately has implications so many discourses that are untouchable which then made criticism by the public through print media.